Dynamic Model-Free and Model-Fitting Kinetic Analysis during Torrefaction of Oil Palm Frond Pellets - Sharmeela Matali; Norazah Abd Rahman; Siti Shawalliah Idris; Nurhafizah Yaacob (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2020)
Torrefaction is a thermal conversion method extensively used for improving the properties of biomass. Usually this process is conducted within a temperature range of 200-300 °C under an inert atmosphere with residence time up to 60 minutes. This work aimed to study the kinetic of thermal degradation of oil palm frond pellet (OPFP) as solid biofuel for bioenergy production. The kinetics of OPFP during torrefaction was studied using frequently used iso-conversional model fitting (Coats-Redfern (CR)) and integral model-free (Kissinger-Akahira-Sunose (KAS)) methods in order to provide effective apparent activation energy as a function of conversion. The thermal degradation experiments were conducted at four heating rates of 5, 10, 15, and 20 °C/min in a thermogravimetric analyzer (TGA) under non-oxidative atmosphere. The results revealed that thermal decomposition kinetics of OPFP during torrefaction is significantly influenced by the severity of torrefaction temperature. Via Coats-Redfern method, torrefaction degradation reaction mechanism follows that of reaction order with n = 1. The activation energy values were 239.03 kJ/mol and 109.28 kJ/mol based on KAS and CR models, respectively. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).